Atención prenatal en adolescentes embarazadas - Barbosa Martínez, Rosalva del Carmen; Benavides Torres, Raquel Alicia; Ramírez Aranda, José Manuel (Universidad Autónoma de Nuevo León, 2018)
Introduction: The prevention of pregnancy in adolescence is of great social relevance because of it emotionally, physically and economically affects the adolescent and the family. Furthermore, the children of adolescent mothers have a greater risk of negative events during their lives. It has been reported that 59% of teenage pregnancies are unplanned. Therefore, there is a greater probability of partner and child abuse, careless child care, economic difficulty, loneliness, school desertion, having an unwanted marriage, and a modified or destroyed life project. Objective: To determine the profile of pregnant adolescents who come for prenatal care. Methodology: This was a descriptive cross-sectional study of 60 pregnant adolescents who came for prenatal care in the metropolitan area of a city in northeast Mexico. Results: Mean age was 16 years. Of the participants, 75.7% were in their third trimester of pregnancy. The mean age of first sexual encounter was 15 (12 -17) years and 61.7% mentioned having one sexual partner; 56.7% said this was an unplanned pregnancy. The predominant level of education was completed secondary school (40%); 50% had a common law relationship, 85% said they were housewives, and 41.7% had complications during their pregnancy. Conclusion: Adolescent pregnancy requires special health care since it has a greater risk of complications. Half of the pregnancies in this stage of life are unplanned, a finding that could affect the life and life project of adolescents.